2006
DOI: 10.4141/p05-227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth regulators on the tuberisation and physiological age of potato (Solanum tuberosum L.) tubers grown from true potato seed

Abstract: The effects of plant growth regulators [6-benzyl amino purine (BA), indole-3-acetic acid (IAA), 2,4-dichlorophenoxyacetic acid (2,4-D), gibberellic acid (GA 3 ), chlormequat chloride (CCC), daminozide] and their time of application on tuberisation and physiological age of cv. Chacasina F 1 grown from true potato seed (TPS) were studied in four experiments conducted in spring or autumn in Greece. BA, IAA and 2,4-D did not affect plant development, tuberisation or the physiological age of the tubers produced. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Plants from TPS exhibit a longer period of juvenility12 than plants from seed tubers, as indicated by their production of five or six simple leaves prior to the formation of compound leaves,24 whereas plants from seed tubers form only compound leaves. The application of GA 3 to plants from TPS has been shown to increase leaf area mainly as a result of increased leaf size,12 whereas GA 3 increases leaf number in plants from seed tubers 15.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants from TPS exhibit a longer period of juvenility12 than plants from seed tubers, as indicated by their production of five or six simple leaves prior to the formation of compound leaves,24 whereas plants from seed tubers form only compound leaves. The application of GA 3 to plants from TPS has been shown to increase leaf area mainly as a result of increased leaf size,12 whereas GA 3 increases leaf number in plants from seed tubers 15.…”
Section: Resultsmentioning
confidence: 99%
“…Plants from TPS exhibit a longer period of juvenility12 than plants from seed tubers, as indicated by their production of five or six simple leaves prior to the formation of compound leaves,24 whereas plants from seed tubers form only compound leaves. The application of GA 3 to plants from TPS has been shown to increase leaf area mainly as a result of increased leaf size,12 whereas GA 3 increases leaf number in plants from seed tubers 15. Moreover, repeated applications of GA 3 to plants from TPS initiated early in the growth cycle cause an increase in tuber number per plant,16 whereas in plants from seed tubers the tuber number per plant is decreased by repeated GA 3 applications 15.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in WM and DM when compared to the control could be explained by the work of Alexopoulos, Akoumianakis, and Passam (2006) who argued that the effects of cytokinins on increasing increase cell division and reducing tuber dormancy depend on the PA of the mother tubers. Villafranca et al, (1998) concluded that under in vitro conditions the PA of the mother tubers had a significant effect on responses in terms of microtuberization, confirming the importance of the PA throughout the process; however, in our study it was not possible to know the PA of the genotypes at the beginning of the assays.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory issues relating to the use of Cq have been reviewed by the US EPA (Anonymous 2007b). Much is known about its mode of action (Hughes 1967;Tolbert 1960), distribution in treated plants (Dekhuijz and Vonk 1974), effect on crop yield (Alexopoulos et al 2006;Berry et al 2004;Browne et al 2006;Espindula et al 2009;Gencsoylu 2009;Leitch and Kurt 1999) and residue concentration in food and agricultural products (Granby and Vahl 2001;Juhler and Vahl 1999;Zhao et al 2000;Ueberschar et al 2003). No studies have yet been published on the environmental fate of Cq and the contamination risk it may pose to the aquatic environment, however.…”
mentioning
confidence: 98%